PENGARUH FAKTOR FUNDAMENTAL DAN TEKNIKAL PENYALURAN KREDIT MODAL KERJA (Studi Empiris Bank Konvensional yang Terdapat Di BEI) - Sutrisno, Sutrisno; Putri, Rissa Suseno (Fakultas Ekonomi, Program Studi Akuntansi, 2018)
This study aims to determine the determinants of working capital loan distribution. Factors suspected of having an effect on distribution of working capital loan are fundamental factors consist of capital as measured by the Capital Adequacy ratio (CAR), credit risk measured by Non Performing Loans (NPL), liquidity risk measured by the Loan To Deposit Ratio (LDR), operating risk as measured by Operational Expenses on Operating Income ratio (BOPO), while technical factors consist of interest rates and inflation. While distribution of working capital loans are measured by the natural logarithm of the amount of working capital loans. The research population is banks listed on the Stock Exchange during 2014-2017 with a sample of 20 banks taken using the purposive sampling method. The analytical method used in this study is multiple linear regression. The results of this study indicate that Capital Adequacy ratio, Loan To Deposit Ratio, and Operational Expenses on Operating Income ratio have a negative and significant effect on working capital loan, Non Performing Loans has a positive and significant effect on working capital loan, while interest rates and inflation have no effect on working capital loan.